Root Couse Analysis (RCA) and Plan Internal Quality Audit Results Corrective Action - Sarlota Singerin (Peneliti.net, 2021)
Nationally, the quality of secondary education in Indonesia has not been as expected. The results of the quality mapping based on data from the Directorate General of Primary and Secondary Education show that only about 16% of education units meet the National Education Standards (SNP). Most of the other education units have not met the SNP, in fact there are a number of education units that still do not meet the minimum service standards (SPM). This study aims to: describe the quality management, find the causes and root problems associated with the findings of the Internal Quality Audit and provide recommendations and suggestions on corrective measures that can be used as solutions to problems found at YPKPM Ambon Christian Senior High School. This study uses the Root Cause Analysis method